2022
DOI: 10.1126/scitranslmed.abn4342
|View full text |Cite
|
Sign up to set email alerts
|

The trillion dollar vaccine gap

Abstract: New technologies and unprecedented public investment have transformed vaccine development and allowed fast delivery of safe and efficacious COVID-19 vaccines, mitigating the impact of the pandemic on health and the economy. A quantum change in public investment for vaccine development and widespread vaccine distribution are necessary to achieve global pandemic preparedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…While the current US administration had proposed an Apollo-style pandemic preparedness plan, which includes strengthening the public health system with a 'particular focus on reducing inequities' and will cost US $65.3 billion over the next ten years, 16 this investment maybe insu cient to address social and welfare damage resulting from COVID, especially for Hispanic and non-Hispanic Black communities that have been disproportionately impacted. While estimates the optimal investment in pandemic preparedness vary, any set of interventions that optimize access for care for vulnerable populations and strengthens technological, surveillance, clinical, manufacturing, and regulatory capacities to respond future pandemics is likely to cost hundreds of billions of dollars 17 . Nonetheless, weighed against the full income losses outlined in this paper, such investments are likely to yield a substantial dividend.…”
Section: Resultsmentioning
confidence: 99%
“…While the current US administration had proposed an Apollo-style pandemic preparedness plan, which includes strengthening the public health system with a 'particular focus on reducing inequities' and will cost US $65.3 billion over the next ten years, 16 this investment maybe insu cient to address social and welfare damage resulting from COVID, especially for Hispanic and non-Hispanic Black communities that have been disproportionately impacted. While estimates the optimal investment in pandemic preparedness vary, any set of interventions that optimize access for care for vulnerable populations and strengthens technological, surveillance, clinical, manufacturing, and regulatory capacities to respond future pandemics is likely to cost hundreds of billions of dollars 17 . Nonetheless, weighed against the full income losses outlined in this paper, such investments are likely to yield a substantial dividend.…”
Section: Resultsmentioning
confidence: 99%
“…Since the development of the smallpox vaccine( 39 ), using cowpox-like virus as the immunogen, three generations of the related VACV-based-smallpox vaccines have been developed( 1, 40, 41 ). However, over the past decade, a large number of newer vaccine platforms have emerged that are able to drive robust humoral and cellular immunity( 42, 43 ), including the mRNA vaccine platform, able to rapidly and flexibly deliver pathogen-antigens to the immune system to drive immunity. While attenuated pathogens induce immunity against the complete pathogen, current mRNA vaccination only delivers components of the target pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The broader health effects (B) including the mental health impact of the COVID-19 pandemic and related social restrictions, the overload on health systems, the disproportional direct/indirect health burden of disadvantaged groups in the society associated with the pandemic, were well documented [39][40][41][42][43][44][45][46]. However, limited evidence was identified to assess the monetary value of vaccination through its impact on mental health or considering the health equity aspect of the pandemic or vaccination [47][48][49]. While certain elements of the public finance impact of the pandemic (C) have been estimated for both the US and UK, no study was identified calculating the full public finance impact or the return on investment of the COVID-19 vaccines [18,50,51].…”
Section: Identified Quantification Methodsmentioning
confidence: 99%